Guillain-Barre syndrome in patients receiving chimeric antigen receptor T-cell therapy: an individual participant data meta-analysis - Kilroe, Kathleen M.; Clarke, Jamie E.; Ann, Phoebe; Salamon, Noriko; Acharya, Jay (Frontiers in Neurology, 2025)
Chimeric antigen receptor (CAR) T-cell therapy has revolutionized the treatment of hematologic malignancies but is increasingly associated with unique neurotoxic complications. While cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS) are well-characterized, Guillain-Barré syndrome (GBS) remains a rare and underrecognized adverse event. This PRISMA-guided systematic review, supplemented by a novel case report, outlines the clinical, radiographic, and diagnostic characteristics of GBS following CAR T-cell therapy. A total of 10 cases were evaluated, including a case from our institution involving a 30-year-old male with high-grade B-cell lymphoma who developed GBS with lasting neurological deficits despite treatment. Across reported cases, the onset of GBS ranged from 5 to 78 days following CAR T-cell infusion and was frequently preceded by CRS. Notably, 60% of patients exhibited facial nerve involvement, with cranial neuropathies often preceding peripheral symptoms, an atypical presentation that differs from classic GBS. Radiographic imaging often demonstrated facial nerve enhancement, while cerebrospinal fluid analysis revealed albuminocytologic dissociation with mild pleocytosis. Although intravenous immunoglobulin (IVIG) was the mainstay treatment, clinical responses were limited, raising questions about pathophysiology. Unlike classic GBS, which is typically antibody-mediated, CAR T-cell–associated GBS may stem from non-specific immune activation and cytokine-driven bystander injury. This review suggests CAR T-cell–related GBS may represent a distinct clinical entity with unique radiologic findings. Early recognition and further mechanistic investigation are essential to guide effective management.